2015
DOI: 10.1088/2053-1583/2/3/031001
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of an exfoliated monolayer graphene flake onto an optical fiber end face for erbium-doped fiber laser mode-locking

Abstract: This paper presents, for the first time, the successful transfer of exfoliated monolayer graphene flake to the optical fiber end face and alignment to its core. By fabricating and optimizing a polymeric poly (methyl methacrylate) (PMMA) and polyvinyl alcohol (PVA) substrate, it is possible to obtain a contrast of up to 11% for green light illumination, allowing the identification of monolayer graphene flakes that were transferred to optical fiber samples and aligned to its core. With Raman spectroscopy, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Our method is based on a wet transfer of the patterned resist lm with polyvinyl alcohol (PVA) as used similarly for transferring exfoliated 2D materials. 21,22 Floating transfer in itself is not a new concept but is used in various applications based on different protocols, e.g. the transfer of photonic crystals 23,24 and anodic aluminum oxide templates.…”
Section: Introductionmentioning
confidence: 99%
“…Our method is based on a wet transfer of the patterned resist lm with polyvinyl alcohol (PVA) as used similarly for transferring exfoliated 2D materials. 21,22 Floating transfer in itself is not a new concept but is used in various applications based on different protocols, e.g. the transfer of photonic crystals 23,24 and anodic aluminum oxide templates.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, most research has only demonstrated functional 2D materials transferred on curved surface. 7,13,14 Without device configuration, controlling, monitoring, and reading signals of those 2D functional layers are difficult. It is thus of great importance to devise a technique that can integrate 2D materials device assemblies, for advanced functionalities on surfaces.…”
mentioning
confidence: 99%
“…wrapped graphene onto a stripped optical fiber to modulate optical signals with optical source . In addition, transferred graphene on an optical fiber can be used for passive mode-locking. , Combining those features of 2D materials and their devices, the feasible potential of integrating functional 2D optoelectronic devices onto various nonflat surfaces thus comes into existence.…”
mentioning
confidence: 99%
See 2 more Smart Citations